Juridical Analysis Regarding The Settlement of Land Disputes of The Heirs with The Government (Verdict Number: 2862/K/Pdt/1994) - Najla Fadhila; Juven Charlos Sagala (IHSA Institute, 2021)
Land is a very important role in the community. In Indonesia, the problem of land is quite common, and it is referred to as land disputes in court. Land disputes are issues that occur between people or legal organizations and institutions that do not have a large socio-political impact. Researchers analyze further with the problem raised, which are the document can evidence of ownership of land be won in court, and judge's consideration in determining land disputes in Verdict Number: 2862.K/Pdt/1994. The sort of analysis that the researcher employs is normative juridical in nature. The intention of this analysis is to find what constitutes evidence of ownership of land rights, under the norms of law. As well as the judge's conclusion in court disputes, using legal sources such as No. 5 of 1960, PP No. 10 of 1961, and PP No. 24 of 1997. This study concludes that to win land disputes in court, physical possession with a period of more than 20 years in good faith, accompanied by written evidence such as a letter of evidence from the headman of the village.